860 fs GdVO4 Raman laser at 1228 nm pumped by 36 ps, 1063 nm laser. (9th July 2019) - Frank, M; Smetanin, S N; Jelínek, M; Vyhlídal, D; Shukshin, V E; Zverev, P G; Kubeček, V
Abstract: The first femtosecond crystalline Raman laser pumped by a picosecond laser is demonstrated. The method consisted of a synchronously pumped cascade SRS process. This process is started with extracavity Raman conversion from pump radiation into the long-shifted Stokes component and continues with secondary intracavity Raman conversion from the long-shifted Stokes component into the Stokes component with combined long and short Raman shift. This secondary conversion shows strong pulse shortening down to the inverse width of the widest short-shift Raman line. We report characteristics of the all-solid-state extracavity Raman laser based on the 16 mm long a-cut GdVO4 crystal under synchronous pumping by the 1063 nm 36 picosecond 150 MHz Nd:GdVO4 laser. Cascade two-wavelength Raman generation in the external high-Q ring cavity has been obtained not only at the usual wavelength of 1174 nm corresponding to the long-shifted first Stokes component, but also at the unusual wavelength of 1228 nm having the combined long and short Raman shift. The individual pulse energy of the 1228 nm radiation was up to 10 nJ and slope efficiency of 5%. Significant shortening of the 36 ps pump pulse down to 860 fs at 1228 nm has been demonstrated without using any compressor.